A Theoretical, Empirical, and Methodologically Based Instrument to Assess the Risk of Violent Jihadist Radicalization in Prisons: The DRAVY-3 - González-Álvarez, José Luis (Terrorism and political violence, 2024)
A main goal of the Spanish National Counter-Terrorism Strategy is to improve the detection and control of inmates who may participate or collaborate with terrorist groups after release convicted and detained inmates linked to terrorist acts, as well as of those individuals involved, during their stay in prison, in violent extremist recruitment or indoctrination. This manuscript introduces an instrument for assessing the risk of violent jihadist radicalization in prisons, the Detention of Violent Jihadists Radicalization (DRAVY-3 for its Spanish initials). This instrument was built on tools already existing, a review of the literature, the experience of the prison staff, indicators suggested by researchers from two institutions, a field study conducted with Muslim inmates (jihadists and non-jihadists), and the results of six implementations of two preliminary versions. The DRAVY-3 was tested by evaluating 570 inmates from five groups (related to jihadist terrorism and controls). The analyses showed that the indicators are distributed into three scales: violence in general, violence of jihadist aetiology, and radicalism. Analyses also informed that a combination of indicators confirm an index of prediction of the level of danger. Results demonstrate the internal strength of the instrument and its capacity to detect potential radicalization leading to violence.